Current Practice and New Developments in Trauma - Kin-Yan, Lee; Cheng, Mina (Cambridge Scholars Publishing, 2021)
This book provides concise and updated information on trauma, consisting of current evidence-based techniques, practical guidelines, and new concepts and advancements in the field, including decision making from the golden hour to definitive treatment. It can serve as a reference book for doctors and those sitting for professional examinations, including general surgeons, orthopaedic surgeons, cardiothoracic surgeons, anaesthesiologists, neurosurgeons, radiologists, urologists, intensivists, and emergency physicians. It is also suitable for medical students and nurses.